What means sustainability and sustainable development? (Ökologisches Wirtschaften - Fachzeitschrift, 2010)
What is the meaning of the terms sustainable development and sustainability? Although both terms have general positive connotation, there remains a difference between the connotation of sustainable development and sustainability. These differences are particularly true for people that do not know the terms.